2012
DOI: 10.1002/anie.201202043
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of a Non‐Natural Amino Acid into a Nonribosomal Peptide Antibiotic by Modification of Adenylation Domain Specificity

Abstract: Calcium-dependent antibiotics (CDA) are cyclic lipopeptides assembled by nonribosomal peptide synthetase (NRPS) enzymes. Active site modification of the 3-methyl glutamate activating adenylation (A) domain of the CDA NRPS enables the incorporation of synthetic 3-methyl glutamine into CDA. This provides the first example of how A-domains can be engineered to introduce synthetic "non-natural" amino acids into nonribosomal peptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0
8

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 33 publications
0
87
0
8
Order By: Relevance
“…10 However, the former method characterizes only the first half-reaction catalyzed by an A domain (i.e., the acyl-adenylate formation reaction), but not the second half-reaction (i.e., the thioesterification reaction involving an ACP domain). Therefore, an apparent active substrate in this assay may form only an acyl adenylate intermediate that cannot be transferred to the ACP domain for subsequent reactions.…”
Section: Introductionmentioning
confidence: 99%
“…10 However, the former method characterizes only the first half-reaction catalyzed by an A domain (i.e., the acyl-adenylate formation reaction), but not the second half-reaction (i.e., the thioesterification reaction involving an ACP domain). Therefore, an apparent active substrate in this assay may form only an acyl adenylate intermediate that cannot be transferred to the ACP domain for subsequent reactions.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the specificity of the A domain of module 10 within the calcium-dependent antibiotic (CDA) NRPS was modified by the introduction of a single mutation (Lys278Gln), changing its specificity from (2 S ,3 R )-3-methyl Glu (mGlu)/Glu to (2 S ,3 R )-3-methyl Gln (mGln)/Gln to produce the Gln/mGln-containing CDA analogues ( 14 – 15 ) (Fig. 1) 24 . A similar point mutation in the Phe-specific A domain of the gramicidin synthetase GrsA (Trp239Ser) allowed for the introduction of an O -propargyl-Tyr residue 25 .…”
Section: Expanding Enzymatic Diversitymentioning
confidence: 99%
“…NRPS enzymes seem to be more discerning of nonnative substrates than the ribosome for protein biosynthesis. While early work showed that downstream modules may block the elongation of peptide intermediates with the incorporation of nonnative substrates (Pavela-Vrancic et al, 1999; Uguru et al, 2004), more recent studies have successfully demonstrated the ability of reprogrammed A-domains to incorporate nonnative substrates into the final NRPs (Evans et al, 2011; Fischbach et al, 2007; Thirlway et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…In an effort to alleviate these problems, Walsh and coworkers used directed evolution to improve the activity of chimeric assembly lines, which led to nearly 10-fold improvements in catalytic activity (Fischbach et al, 2007). A complimentary approach to reengineer A-domain specificity preserving the native protein-protein interactions within an NRPS module has been to use the nonribosomal peptide code and, more recently, computational structure-based redesign to rationally mutate residues important for substrate recognition (Chen et al, 2009; Eppelmann et al, 2002; Thirlway et al, 2012). In order to screen potential mutants more comprehensively, Kelleher and co-workers developed a novel workflow involving directed evolution to create a library of ~1,000 mutants based on the “nonribosomal peptide code” and mass spectrometry to measure the ability of the resulting mutants to support production of novel NRPs (Evans et al, 2011).…”
Section: Introductionmentioning
confidence: 99%